2015
DOI: 10.3791/52438
|View full text |Cite
|
Sign up to set email alerts
|

Bile Duct Ligation in Mice: Induction of Inflammatory Liver Injury and Fibrosis by Obstructive Cholestasis

Abstract: In most vertebrates, the liver produces bile that is necessary to emulsify absorbed fats and enable the digestion of lipids in the small intestine as well as to excrete bilirubin and other metabolic products. In the liver, the experimental obstruction of the extrahepatic biliary system initiates a complex cascade of pathological events that leads to cholestasis and inflammation resulting in a strong fibrotic reaction originating from the periportal fields. Therefore, surgical ligation of the common bile duct h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
214
0
6

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 221 publications
(227 citation statements)
references
References 20 publications
7
214
0
6
Order By: Relevance
“…BDL is a well-known model of biliary fibrosis where the bile outflow from the liver is interrupted and the bile accumulates in the bile ducts. 13 The backpressure and toxicity of bile acids are the major causes of proliferation of the duct cells and their spreading into liver parenchyma. Subsequently, Kupffer cells migrate to the bile ducts causing portal inflammation and necrosis, thus leading to fibrosis.…”
Section: Models To Target Cholangiocytesmentioning
confidence: 99%
See 1 more Smart Citation
“…BDL is a well-known model of biliary fibrosis where the bile outflow from the liver is interrupted and the bile accumulates in the bile ducts. 13 The backpressure and toxicity of bile acids are the major causes of proliferation of the duct cells and their spreading into liver parenchyma. Subsequently, Kupffer cells migrate to the bile ducts causing portal inflammation and necrosis, thus leading to fibrosis.…”
Section: Models To Target Cholangiocytesmentioning
confidence: 99%
“…9,10 Expression of MMPs in the liver is not restricted to a certain cell type; they are produced by Kupffer cells, all immune cells, 11,12 HSCs, cholangiocytes, 13 as well as hepatocytes. 14 MMPs act as a part of a proteolytic network, in which proteases activate each other by processing inactive proforms.…”
mentioning
confidence: 99%
“…We used the CCl 4 -induced liver fibrosis model because it simulates SI-induced pathology and is a reproducible model, 34 whereas the commonly used bile-duct ligation model requires surgery and can often be associated with mortality and platelet activation associated with surgery. 35 Although our model involves an artificial and aggressive liver injury, other natural chronic liver injury models should be tested in the future to assess the role of platelet-derived TGF-b1 in models of alcohol-induced, acetaminophen overdose-induced, and viral or parasite infection-induced liver fibrosis. 34 Recently, Ito et al have shown that platelets can pass through toxininduced injured liver sinusoidal endothelial layers.…”
Section: Pf4cretgfb1mentioning
confidence: 99%
“…Effects of bile acids on platelet activation have also been suggested [26]. In the last decades, several experimental rodent models of acute and chronic hepatic failure have been established, for example the experimental obstruction of the extrahepatic biliary system known to initiate a complex cascade of pathological events leading to cholestasis and inflammation [27]. A most commonly used model is the surgical ligation of the common bile duct (bile duct ligation, BDL) to induce obstructive cholestatic injury in rodents instrumental for the analysis of molecular and cellular events that underlie the pathophysiological mechanisms induced by inappropriate bile flow [27].…”
Section: Introductionmentioning
confidence: 99%
“…In the last decades, several experimental rodent models of acute and chronic hepatic failure have been established, for example the experimental obstruction of the extrahepatic biliary system known to initiate a complex cascade of pathological events leading to cholestasis and inflammation [27]. A most commonly used model is the surgical ligation of the common bile duct (bile duct ligation, BDL) to induce obstructive cholestatic injury in rodents instrumental for the analysis of molecular and cellular events that underlie the pathophysiological mechanisms induced by inappropriate bile flow [27]. Here we used this model of complete obstruction of the common bile duct and analyzed altered platelet function and the underlying mechanisms in the acute and sub-acute phase after injury to study the consequences of cholestatic liver disease on hemostasis.…”
Section: Introductionmentioning
confidence: 99%